The Influence of Transformational Leadership and Work Motivation on Employee Performance at PT. ABC - Syech Khan Fahri Alfaribi; Agung Surya Dwianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study is motivated by the phenomenon of performance gaps at PT. ABC, as indicated by the suboptimal realization of sales targets (83–84%) and issues with Service Response Time (SRT) exceeding company standards. These conditions are strongly suspected to be influenced by unstable transformational leadership and work motivation factors. The purpose of this study is to analyze the effect of transformational leadership and work motivation on employee performance at PT. ABC, both partially and simultaneously, using a quantitative approach with a causal associative method. The population in this study consists of all 53 employees of PT. ABC, with the sampling technique using saturated sampling or census. Data were collected through questionnaires using a Likert scale that has been tested for validity and reliability, and then analyzed using multiple linear regression with the assistance of SPSS software. The results show that simultaneously, transformational leadership and work motivation have a positive and significant effect on employee performance, with a contribution of 83.9%. Partially, work motivation is found to be the most dominant variable influencing employee performance compared to leadership style, indicating that internal drive is a stronger factor in maintaining work quality and service timeliness. In conclusion, the synergy between inspirational leadership vision and strong motivation is proven to reduce operational obstacles within the company. Therefore, management is recommended to prioritize strengthening motivational aspects to ensure the achievement of overall organizational strategic targets.